2020
DOI: 10.21203/rs.3.rs-35490/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vancomycin-lock therapy for prevention of catheter-related bloodstream infection in very low body weight infants

Abstract: Background: This study was to evaluate the effectiveness and safety of vancomycin- lock therapy for the prevention of catheter-related bloodstream infection (CRBSI) in very low body weight (VLBW) preterm infant patients.Methods: One hundred and thirty-seven cases of VLBW preterm infants who retained peripherally inserted central catheters (PICCs) were retrospectively reviewed, including 68 treating with heparin plus vancomycin (vancomycin-lock group) and 69 with heparin only (control group). The incidence of C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Peripherally inserted central catheters (PICCs) are widely used in neonatal intensive care units (NICUs), especially for the treatment of extremely preterm infants and very low birth weight (VLBW) infants to provide secure venous access or safe administration of hyperosmolar solutions [1] . However, the use of PICCs increases the risk of catheter-related bloodstream infection (CRBSI), one of the most common nosocomial infections related to PICCs [2,3] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripherally inserted central catheters (PICCs) are widely used in neonatal intensive care units (NICUs), especially for the treatment of extremely preterm infants and very low birth weight (VLBW) infants to provide secure venous access or safe administration of hyperosmolar solutions [1] . However, the use of PICCs increases the risk of catheter-related bloodstream infection (CRBSI), one of the most common nosocomial infections related to PICCs [2,3] .…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of PICCs increases the risk of catheter-related bloodstream infection (CRBSI), one of the most common nosocomial infections related to PICCs [2,3] . CRBSI was associated with several lifethreatening complications, including necrotizing enterocolitis (NEC), intraventricular hemorrhage (IVH), bronchopulmonary dysplasia (BPD), and retinopathy of prematurity (ROP), extended the hospital stay and the increased mortality or morbidity of premature infants [1,4] . It have been reported that bacteria were the most important pathogen of CRBSI [5] .…”
Section: Introductionmentioning
confidence: 99%